Are We Still Illyrians? - Higgins, Valerie (Ex Novo: Journal of Archaeology, 2016)
This paper examines the changing attitudes of young Albanian archaeologists to Albania’s archaeological heritage. As Cold War archaeologists retire and are replaced by a generation trained after the fall of communism, this paper asks how their different world perspective will influence the future direction of archaeology. Particular issues that are addressed are the perceived role of the Illyrians in national identity and the willingness of young archaeologists to embrace new types of heritage sites, such as industrial and Cold War archaeology. Examples of the latter are very prominent in the Albanian landscape, but their interpretation and incorporation into the national narrative are still contentious issues for many.